Mitophagy in the mechanisms of treatment resistance in solid tumors - Xiaoyi Yan; Hui Ding; Mengxiao Ren; Lei Zang (Oncology Reviews, 2025)
This review aims to explore the mechanisms by which mitophagy contributes to treatment resistance in solid tumors. As advancements in cancer therapies continue to evolve, treatment resistance emerges as a significant barrier to successful tumor management. Mitophagy, a specific form of cellular autophagy, has been implicated in the survival, proliferation, and drug resistance of tumor cells. This article will summarize the latest research findings and analyze how mitophagy impacts the biological characteristics of solid tumors, thereby revealing its potential implications in cancer treatment strategies. By understanding the role of mitophagy in the context of treatment resistance, we may uncover new therapeutic targets and strategies to enhance the efficacy of existing cancer treatments.